Diseño de equipo electrohilado por método centrifugado para polímeros. - Torres Martínez, Jhonathan Vladimir (Universidad Antonio Nariño, 2021)
The application of the centrifugal electrospinning technique allows the electric field and the centrifugal force to be used simultaneously, achieving a production of polymeric nanofibers in greater volume and less time, making its way both in industry and in research centers. For this reason, the design of a centrifugal electrospinning equipment was proposed that combines the characteristics of the conventional method with the application of centrifugal force to exceed the level of productivity